MUHAMMADIYAHS THOUGHTS ON BANK INTEREST: AN ANALYSIS OF THE IJTIHAD METHOD - Ana Cahayani Fatimah; Waode Kasriawati Bakari; Fatmawaty Padedeng; Suwarno Djodding; Mahsyar Idris (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2026)
This study aims to examine Muhammadiyah's thinking on bank interest through the analysis of the ijtihad method used in determining bank interest law in the perspective of contemporary Islam. The issue of bank interest is an issue that continues to be debated in Islamic economic discourse because it is related to the practice of usury, the development of the modern financial system, and the public's need for banking institutions. This research uses a qualitative approach with a type of library research and a normative-philosophical approach. Data were obtained from official documents of Muhammadiyah, fatwa of the Tarjih and Tajdid Councils, scientific journals, books, and relevant academic articles. The data collection technique is carried out through documentation and literature study, while the data analysis technique uses data reduction, classification, interpretation, and drawing conclusions in a deductive-analytical manner. The results of the study show that Muhammadiyah views bank interest as an ijtihadiyah issue that is decided through the bayani, burhani, and istislahi approaches. Muhammadiyah tends to prohibit bank interest because it is considered to have additional elements that are close to usury, but still considers the benefits and socio-economic conditions of modern society. The findings of the study show that there is a moderate ijtihad pattern of Muhammadiyah that seeks to integrate normative texts with contemporary economic realities. This research contributes to the development of an Islamic economic ijtihad methodology that is more adaptive to the dynamics of the modern financial system.